Employment Restrictions and Political Violence in the Israeli-Palestinian Conflict - Sami Miaari; Asaf Zussman; Noam Zussman (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
Following the outbreak of the Second Intifada in 2000, Israel imposed severe restrictions on the employment of Palestinians within its borders. We study the effect of this policy change on the involvement of West Bank Palestinians in fatal confrontations during the first phase of the Intifada. Identification relies on the fact that variation in the pre-Intifada employment rate in Israel across Palestinian localities was not only considerable but also unrelated to prior levels of involvement in the conflict. We find robust evidence that localities that suffered from a sharper drop in employment opportunities were more heavily involved in the conflict.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: F52; H56; J23; J48; 330; Employment Restrictions; Political Violence; Israeli-Palestinian Conflict